Social acceptance levels of normal developed students towards disable students - Buse Özlü; Nergüz Bulut Serin (International Journal of Evaluation and Research in Education (IJERE), 2021)
The study aimed to examine whether there is a significant difference between the social acceptance levels of the students with disabilities in the middle school students with normal development according to the variables of gender, grade level, number of siblings, and income level. This study was carried out in general screening model with appropriate sampling model. The universe of this research consists of 6th and 7th grade students. The sample of the study consists of 220 students. Social acceptance scale was used to collect data. One-way analysis of variance (t-test) were calculated using test techniques. As a result of the research, it was observed that the average score of peer attitude of female students was higher than male students. No significant difference was found between the social acceptance scale subscales, social skills, and student behavior subscales and social acceptance scale total scores of students with normal development according to their grade level. According to the number of participants’ siblings, a significant difference was found between the student behavior subscale of the social acceptance scale and the total score averages of the social acceptance scale.